Impacts of taxonomic inertia for the conservation of African ungulate diversity: an overview. (21st April 2017) - Gippoliti, Spartaco; Cotterill, Fenton P. D.; Zinner, Dietmar; Groves, Colin P.
ABSTRACT: We review the state of African ungulate taxonomy over the last 120 years, with an emphasis on the introduction of the polytypic species concept and the discipline's general neglect since the middle of the 20th century. We single out negative consequences of 'orthodox' taxonomy, highlighting numerous cases of neglect of threatened lineages, unsound translocations that led to lineage introgression, and cases of maladaptation to local conditions including parasitic infections. Additionally, several captive breeding programmes have been hampered by chromosome rearrangements caused by involuntary lineage mixing. We advocate that specimen‐based taxonomy should regain its keystone role in mammal research and conservation biology, with its scientific values augmented with genomic evidence. While integration with molecular biology, ecology and behaviour is needed for a full understanding of ungulate alpha diversity, we stress that morphological diversity has been neglected despite its tremendous practical importance for some groups of 'utilizers' such as trophy hunters, wildlife tourists and conservationists. We conclude that there is no evidence that purported 'taxonomic inflation' has adverse effects on ungulate conservation: rather, it is taxonomic inertia that has such adverse effects. We stress that sound science, founded on robust taxonomy, should underpin effective sustainable management (hunting, ranching, captive breeding and reintroduction programmes) of this unique African natural resource.